Comparison between pre-treatment with nalbuphine vis-a-vis dexmedetomidine for prevention of etomidate induced myoclonus - Saha, Manoj Kumar; Banu, Parvin; Mukhopadhyay, Sayantan; Biswas, Arunava; Bhattacharyya, Susmita (Asian Journal of Medical Sciences, 2023)
Background: Etomidate is considered as an excellent drug for induction in anesthesia, although it has an undesirable side effect like myoclonus. Aims and Objectives: The aims of this study were to compare the effect between pre-treatment with nalbuphine and dexmedetomidine for attenuation and severity of etomidate induced myoclonus and to assess their adverse drug reaction. Materials and Methods: A prospective, randomized, and single-blinded study was conducted on patients undergoing elective surgery under general anesthesia. After selection of patients according to inclusion/exclusion criteria, nalbuphine (0.2 mg/kg) and dexmedetomidine (0.5 μg/kg) were infused 10 min before the induction of anesthesia. The vital parameters and any incidences of myoclonus during operation were observed at fixed interval. Results: A total of 102 patients in the age group of 18–60 years of either sex were assessed. In Group D 7, out of 51 patients (13.7%) were found to have myoclonus, whereas, in Group N, it was observed in 21 out of 51 patients (41.2%). Difference between the two was found to be statistically significant (P<0.001). In Group D, grade 3 myoclonus was observed in 0% patients. About 2% patients had grade 2 and 11.8% had grade 3 myoclonus. In Group N, grade 3, 2, and 1 myoclonus was recorded as 3.9%, 11.8%, and 25.5%, respectively. The difference between the two groups is statistically significant (P<0.001). Conclusion: Incidence and severity of etomidate induced myoclonus were less in patients who received pre-treatment with dexmedetomidine than those who underwent pre-treatment with nalbuphine. Furthermore, more hemodynamic stability was achieved with use of dexmedetomidine as the agent for pre-treatment.